The effect of using the guided discovery method in learning to throw the javelin and developing some associated physical abilities (Journal of the College of Basic Education, 2022)
The research aimed to identify the effect of using the guided discovery method in learning and developing some physical abilities related to the effectiveness of javelin throwing for third-stage students in the Department of Physical Education compared to the usual teaching method. The experimental approach was used, and the research sample was selected from third-stage students in the Department of Physical Education, College of Basic Education, University Al-Mustansiriya The results revealed that teaching by the method of directed discovery contributed to improving learning the effectiveness of javelin throwing and developing the physical capabilities related to the effectiveness of the members of the research sample. It was recommended to use the method of guided discovery in learning the effectiveness of javelin throwing and developing some physical abilities associated with this activity